The rise and fall of Corbynism - Cop, Burak; Ertürk, Ahmet Cemal (İstanbul Bilgi Üniversitesi Yayınları, 2021)
ABSTRACT: In an era when the traditional centre-left parties have constantly lost ground to rising right-wing populist movements, Jeremy Corbyn’s Labour Party was increasingly portrayed as a left-wing alternative to both pro-austerity incumbent parties that rule out redistributive policies and right-wing populism fuelled by the grievances of the masses targeting the traditional political elites. Corbyn managed to mobilize a vast section of the society by becoming Europe’s biggest left-wing party in terms of membership and increased its votes in the 2017 election, especially by gaining youth support. Nevertheless, the 2019 election constituted an immense fall. Regarding his political discourse both during the electoral campaigns and the serious challenges he faced, Corbyn could be identified as a left-wing populist. To be more specific, Corbyn is a democratic socialist who usually resorted to left-wing populist means within a social democratic party, and failed in his efforts to transform both the British mainstream politics and the Labour in the end.

ÖZET: Geleneksel merkez sol partilerin yükselen sağ popülist hareketlere karşı sürekli zemin kaybettiği bir tarihsel evrede, Jeremy Corbyn'in İşçi Partisi, hem yeniden dağıtım politikalarını dışlayan kemer sıkma yanlısı iktidar partilerine, hem de kitlelerin siyasi elitlere yönelik memnuniyetsizliğinden güç alan sağ popülizme karşı bir sol alternatif olarak tasvir edildi. Britanya İşçi Partisi üye sayısı bakımından Avrupa'nın en büyük sol partisi haline gelerek toplumun geniş bir kesimini harekete geçirmeyi başardı ve 2017 seçimlerinde özellikle gençlerin desteğini alarak oylarını arttırdı. Buna karşılık 2019 seçimleri muazzam bir düşüşe sahne oldu. Corbyn, seçim kampanyaları sırasındaki siyasi söylemi ve karşılaştığı zorluklara verdiği yanıtlar bakımından bir sol popülist olarak tanımlanabilir. Daha açık ifade etmek gerekirse, Corbyn, sosyal demokrat bir parti içinde genellikle sol popülist araçlara başvuran ve sonunda hem İngiliz ana akım siyasetini hem de İşçi Partisi'ni dönüştürme çabalarında başarısız olmuş bir demokratik sosyalisttir.
Corbynizmin yükselişi ve çöküşü
Keywords: Social democracy; left-wing populism; democratic socialism; Labour Party; Jeremy Corbyn; Sosyal demokrasi; sol popülizm; demokratik sosyalizm; İngiliz İşçi Partisi